2014
DOI: 10.1371/journal.pone.0113522
|View full text |Cite
|
Sign up to set email alerts
|

Live Birth Sex Ratio after In Vitro Fertilization and Embryo Transfer in China - An Analysis of 121,247 Babies from 18 Centers

Abstract: In order to study the impact of procedures of IVF/ICSI technology on sex ratio in China, we conducted this multi-center retrospective study including 121,247 babies born to 93,895 women in China. There were 62,700 male babies and 58,477 female babies, making the sex ratio being 51.8% (Male: Female  = 107∶100). In univariate logistic regression analysis, sex ratio was imbalance toward females of 50.3% when ICSI was preformed compared to 47.7% when IVF was used (P<0.01). The sex ratio in IVF/ICSI babies was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 26 publications
6
47
3
Order By: Relevance
“…Surprisingly, the sex ratio was significantly higher in group 1 than in groups 2, 3 and 4, and in group 2 compared with group 3 (P < 0.001). Some studies have reported differences in the sex ratio after blastocyst culture, with a higher male to female ratio (Bu et al, 2014;Chang et al, 2009;Maalouf et al, 2014). Moreover, Alfarawati et al (2011) showed that male embryos developed significantly faster than females, and using time-lapse technology.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the sex ratio was significantly higher in group 1 than in groups 2, 3 and 4, and in group 2 compared with group 3 (P < 0.001). Some studies have reported differences in the sex ratio after blastocyst culture, with a higher male to female ratio (Bu et al, 2014;Chang et al, 2009;Maalouf et al, 2014). Moreover, Alfarawati et al (2011) showed that male embryos developed significantly faster than females, and using time-lapse technology.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Orzack et al (2015), ART included both IVF and ICSI, and the sex ratio was determined for the combined IVF-and ISCI-produced embryos. In most previous studies, the sex ratios of IVF-or ICSI-produced embryos/offspring were analyzed separately, and IVF was shown to result in a male-biased sex ratio (Avery et al 1991, Gutierrez-Adan et al 2001, Wrenzycki et al 2002, Dean et al 2010, Maalouf et al 2014, Torner et al 2014, while ICSI resulted in a female-biased sex ratio (Bu et al 2014, Maalouf et al 2014, Tarin et al 2014. Therefore, ICSI and IVF may affect sex ratios via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sex-specific effects of IVF on postnatal metabolism and growth of IVF-conceived offspring has been confirmed in mouse models (Scott et al 2010, Feuer et al 2014). More importantly, recent studies indicate that IVF results in a skewed sex ratio at birth (Dean et al 2010, Bu et al 2014, Maalouf et al 2014, reflecting sex-biased or even specific disruption of embryonic development. Indeed, the suboptimal environment is known to affect the embryonic development in a sex-specific manner as early as the pre-implantation stage, causing either a short-term sex ratio adjustment or more long-term sexspecific effects on adult health (Laguna-Barraza et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They quoted the following sex birth: IVF with a single blastocyst, 56.1% males; IVF with a single cleaved embryo, 51.6 males; ICSI with single blastocyst, 52.5% males; and ICSI with single cleaved embryo, 48.7% males. Recently, Bu et al [25] analyzed the data of 18 IVF centers in China. There were 62,700 male babies and 58,477 female babies, making the sex ratio 51.8% (male/female = 107∶100).…”
Section: Discussionmentioning
confidence: 99%